Microwave discharge as a source of light - Brodsky, Yu.Ya.; Kovalev, N.F.; Perminov, A.O.; Shlepnev, S.P. (Вопросы атомной науки и техники, 2005)
We try to analyze the ways to optimize microwave discharges in a microwave light source. The problem here is that as the discharge starts glowing, electrodynamic properties of the plasma being the load for the microwave source change significantly. During this, the characteristics of the light radiation from the plasma and efficiency of using the microwave energy are far from optimal. We propose a way to solve this problem, which is based on creating a multiresonance electrodynamic system tuning automatically as the value of the plasma load changes, thus providing reasonably good coupling in all regimes of operation of the lamp. Проведено аналіз шляхів оптимізації узгодження мікрохвильового розряду в мікрохвильовому джерелі світла. Проблема зв'язана з тією обставиною, що при розвитку розряду характер навантаження міняється істотно. При цьому відбувається неузгодженість, і енергія не надходить у розряд. Ми пропонуємо шлях рішення цієї проблеми, заснований на використанні багатомодової електродинамічної системи, що автоматично стежить за зміною імпедансу навантаження. Проведен анализ путей оптимизации согласования микроволнового разряда в микроволновом источнике света. Проблема связана с тем обстоятельством, что при развитии разряда характер нагрузки меняется существенным образом. При этом происходит рассогласование, и энергия не поступает в разряд. Мы предлагаем путь решения этой проблемы, основанный на использовании многомодовой электродинамической системы, которая автоматически следит за изменением импеданса нагрузки.